A regulação bancária brasileira: uma análise do custo de observância regulatória e seus efeitos na concessão de crédito aos produtores rurais pós-Lei n. 14.112/20 - Tamburus, Felipe Sene (2024)
This Master's thesis analyzes the main regulatory framework imposed on financial institutions in the exercise of their credit granting activities, especially regarding risk management, with the focus on demonstrating the rationale of the prudential regulation established by the regulator and its application in the day-to-day of financial institutions. To illustrate the applicability of prudential regulation, the work uses the scenario of credit operations aimed at rural producers, in the post-amendment period brought by Law No. 14.112/20 to Law No. 11.101/05. Therefore, in addition to the presentation and analysis of the main prudential regulatory base, the work also examined data related to the judicial recovery of the agribusiness sector, in order to map more generically the historical behavior of the agribusiness sector in case of crisis, as well as public data on credit operations granted to the agribusiness sector in pre and post-reform periods of the judicial recovery law. In conclusion, an analysis will be presented, from the perspective of prudential risk regulation, on the possible effects on credit granting to rural producers